ڕۆڵی ئەشکەوتەکان لە پەرەپێدانی گەشتوگوزار لە پارێزگای سلێمانیدا - دیوانە, پ. ی. د. ئامانج احمد حمدامین; علی, صلاح الدین حسن (Sulaimani Journal for Humanities, 2023)
Caves as a natural phenomenon, has its own importance in terms of tourism, especially in areas where a large area is covered with mountainous environment. Caves are rich in geomorphology, archaeological, historical and religious nature Caves are used for tourism purposes by tourists in many countries around the world, so caves are considered as one of the most important principles of attracting tourists in most countries. Here we have used the method (historical, regional and analytical), and relied on survey forms and field work to obtain data and information, so the aim of this research is to show the role of caves in tourism development The study concluded that Sulaimani province is rich in beautiful and attractive caves that have the ability to attract tourists, but most of the caves are poor in terms of tourism services, which have not yet seen development activities can be invested scientifically As a result, we found that caves are a tourism potential. This study is divided into three main themes, in addition to each of the introduction, conclusions and recommendations.